Novel alternatives to extracellular vesicle-based immunotherapy – exosome mimetics derived from natural killer cells. (12th November 2018) - Zhu, Liya; Gangadaran, Prakash; Kalimuthu, Senthilkumar; Oh, Ji Min; Baek, Se Hwan; Jeong, Shin Young; Lee, Sang-Woo; Lee, Jaetae; Ahn, Byeong-Cheol
Abstract: Exosomes are endogenous nanocarriers that can deliver biological information between cells. They are secreted by all cell types, including immune cells such as natural killer (NK) cells. However, mammalian cells release low quantities of exosomes, and the purification of exosomes is difficult. Here, nanovesicles were developed by extrusion of NK cells through filters with progressively smaller pore sizes to obtain exosome mimetics (NK-EM). The anti-tumour effect of the NK-EM was confirmed in vitro and in vivo . The morphological features of the NK-EM were revealed by transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA) and Western blot. In vitro, the cytotoxicity of the NK-EM to cancer cells (glioblastoma, breast carcinoma, anaplastic thyroid cancer and hepatic carcinoma) was assessed using bioluminescence imaging (BLI) and CCK-8 assay. For in vivo study, a xenograft glioblastoma mouse model was established. The anti-tumour activity of NK-EM was confirmed in vivo by the significant decreases of BLI, size and weight (all p  < .001) of the tumour compared with the control group. Moreover, NK-EM cytotoxicity for glioblastoma cells that related with decreased levels of the cell survival markers p-ERK and p-AKT, and increased levels of apoptosis protein markers cleaved-caspase 3, cytochrome-c and cleaved-PARP was confirmed. All those results suggest that NK-EM exert stronger killing effects to cancer cells compared with the traditional NK-Exo, at the same time, the tumour targeting ability of the NK-EM was obtained in vivo . Therefore, NK-EM might be a promising immunotherapeutic agent for treatment of cancer.